2017
DOI: 10.1371/journal.pone.0176033
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton blooms during austral summer in the Ross Sea, Antarctica: Driving factors and trophic implications

Abstract: During the austral summer of 2014, an oceanographic cruise was conducted in the Ross Sea in the framework of the RoME (Ross Sea Mesoscale Experiment) Project. Forty-three hydrological stations were sampled within three different areas: the northern Ross Sea (RoME 1), Terra Nova Bay (RoME 2), and the southern Ross Sea (RoME 3). The ecological and photophysiological characteristics of the phytoplankton were investigated (i.e., size structure, functional groups, PSII maximum quantum efficiency, photoprotective pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
71
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 88 publications
6
71
1
Order By: Relevance
“…Our observations support the recent trend of changes in the plankton succession that are potentially restructuring trophic relationships in the Antarctic food web (Mangoni et al. ; Rivaro et al. ).…”
Section: Resultssupporting
confidence: 91%
“…Our observations support the recent trend of changes in the plankton succession that are potentially restructuring trophic relationships in the Antarctic food web (Mangoni et al. ; Rivaro et al. ).…”
Section: Resultssupporting
confidence: 91%
“…Normalized to an SRP detection limit of 0.17 ÎŒM, Garwood had an average stoichiometry of 6N:1P:210Si:2Fe. Recent work in the coastal waters of the Ross Sea, north of Taylor Valley found that the mean N:P:Si ratio in the surface mixed layer was observed to be 21.5:1:63 (Mangoni et al, ). Thus, these coastal streams with their enhanced P (relative to N) concentrations may be very consequential in affecting macronutrient stoichiometry during the austral summer.…”
Section: Resultsmentioning
confidence: 99%
“…To avoid this noise, a deep understanding of the factors that influence the class is needed. We, therefore, referred to previous studies [11,[33][34][35][36][37][56][57][58][59][60][61][62][63][64][65][66] on the growth/limitation of phytoplankton that determine CHL in this region and finally selected the predictors.…”
Section: Predictor Selectionmentioning
confidence: 99%
“…In the western Ross Sea including Cape Hallett, distinct phytoplankton blooms are recurrent from year to year during austral spring and summer, especially around the Terra Nova Bay [11,63]. The phytoplankton growth results from the combinations of many factors such as sea ice, temperature, wind, nutrients, and light [37,[64][65][66].…”
Section: Predictor Selectionmentioning
confidence: 99%